1991
DOI: 10.1083/jcb.114.2.343
|View full text |Cite
|
Sign up to set email alerts
|

The human peripheral lymph node vascular addressin is a ligand for LECAM-1, the peripheral lymph node homing receptor.

Abstract: Abstract. The trafficking of lymphocytes from the blood and into lymphoid organs is controlled by tissueselective lymphocyte interactions with specialized endothelial cells lining post capillary venules, in particular the high endothelial venules (HEV) found in lymphoid tissues and sites of chronic inflammation . Lymphocyte interactions with HEV are mediated in part by lymphocyte homing receptors and tissue-specific HEV determinants, the vascular addressins. A peripheral lymph node addressin (PNAd) has been de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
177
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 288 publications
(183 citation statements)
references
References 41 publications
5
177
1
Order By: Relevance
“…The reactivity of HECA-452 with sLex structures is fucose-dependent (14). Accordingly, no precipitation was observed for AD/IgG produced without FTVII, while a reduced but still detectable reactivity with mutants YYA and FFA was observed (Fig.…”
Section: Fig 2 Ligand Activity Of the Amino-terminal Domain Of Endomentioning
confidence: 91%
See 1 more Smart Citation
“…The reactivity of HECA-452 with sLex structures is fucose-dependent (14). Accordingly, no precipitation was observed for AD/IgG produced without FTVII, while a reduced but still detectable reactivity with mutants YYA and FFA was observed (Fig.…”
Section: Fig 2 Ligand Activity Of the Amino-terminal Domain Of Endomentioning
confidence: 91%
“…Even though MECA-79 recognizes only a subregion of the L-selectin determinant, it is function-blocking and recognizes all of the L-selectin ligands identified thus far on a molecular level. It was used in the original identification of "peripheral lymph node addressin" (PNAd), a complex of L-selectin ligands expressed in mouse and human secondary lymphoid organs (12,14). Included in the complex are the aforementioned CD34, podocalyxin, Gly-CAM-1, and endomucin.…”
mentioning
confidence: 99%
“…␣ 4 ␤ 1 binds to endothelial cells via the vascular cell adhesion molecule, VCAM-1, and is mainly mediating lymphocyte migration into sites of inflammation (13) but not to PLN (14). L-Selectin has been identified as a lymphocyte homing receptor mediating binding to and entry into PLN (15). Its ligand, the PLN addressin, is a tissue-specific endothelial cell carbohydrate antigen found on HEV of PLN in adults and at sites of chronic inflammation (16).…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggested that allergic response induced by IgE and mast cells causes preparation for infiltration of lymphocytes, eosinophils, and neutrophils into the bronchial mucosa. In other organs, e.g., intestine, skin, and lymph nodes, tissue-specific adhesion molecules, chemokines, and their receptors that recruit T cells have already been discovered (15)(16)(17)(18)(19). Despite these discoveries, it is not well known how T cells recirculate into the bronchial mucosa in allergic diseases such as asthma.…”
mentioning
confidence: 99%